PENGGUNAAN ALAT PERMAINAN EDUKATIF “KOTAK PINTAR” SEBAGAI MEDIA PEMBELAJARAN SKI DI MADRASAH IBTIDAIYAH - Meilina, Dwi Maya (AL-IHTIRAFIAH: JURNAL ILMIAH PENDIDIKAN GURU MADRASAH IBTIDAIYAH, 2024)
Watch learning is learning delivered by an educator without using any teaching aids. However, students usually do not understand the delivery. In addition, there is SKI learning which covers the history of Islam in the past, the explanation of which is enough to make students abstract. This will create learning that cannot be captured by students. The aim of this research is to improve educators in conveying an explanation and to increase students' understanding or competence in a new concept by requiring a teaching aid. The method used in this research is the literature study method. The results of this discussion include the smart box tool, which is a learning medium that will make students understand SKI learning in class III better. With this, learning in class III can become effective learning.